Non-Isocyanate Polyurethane Soft Nanoparticles Obtained by Surfactant-Assisted Interfacial Polymerization - Bossion, Amaury (Langmuir : the ACS journal of surfaces and colloids, 2017)
Polyurethanes (PUs) are considered ideal candidates for drug delivery applications due to their easy synthesis, excellent mechanical properties, and biodegradability. Unfortunately, methods for preparing well-defined PU nanoparticles required miniemulsion polymerization techniques with a nontrivial control of the polymerization conditions due to the inherent incompatibility of isocyanate-containing monomers and water. In this work, we report the preparation of soft PU nanoparticles in a one-pot process using interfacial polymerization that employs a non-isocyanate polymerization route that minimizes side reactions with water. Activated pentafluorophenyl dicarbonates were polymerized with diamines and/or triamines by interfacial polymerization in the presence of an anionic emulsifier, which afforded non-isocyanate polyurethane (NIPU) nanoparticles with sizes in the range of 200-300 nm. Notably, 5 wt % of emulsifier was required in combination with a trifunctional amine to achieve stable PU dispersions and avoid particle aggregation. The versatility of this polymerization process allows for incorporation of functional groups into the PU nanoparticles, such as carboxylic acids, which can encapsulate the chemotherapeutic doxorubicin through ionic interactions. Altogether, this waterborne synthetic method for functionalized NIPU soft nanoparticles holds great promise for the preparation of drug delivery nanocarriers